Manajemen Komunikasi Proyek: Studi Kasus Perusahaan Berbasis Engineering, Procurement, Construction dan Manufacturing (EPCM) Kawasan Industri Jababeka Cikarang - Annisa Annisa (Institut Teknologi Sains Bandung, 2019)
This study aims to find out how far the role of communication is a success factor of a project and what are the communication variables that support the success of a project. Case studies were conducted at an EPCM-based company in the Jababeka Industrial Estate, PT. IPK. The approach used is qualitative, with methods of observation, interviews, and literature studies. Observation is carried out in order to observe the way the team communicates, interviews carried out on key persona. The literature study was conducted aimed at collecting data and for understanding the study object. Direct observation in the field is carried out without disrupting the project. The results of the study show that the method of electronic communication is an effective method to use. In general, the use of methods for communicating is quite good. Internal information distribution using email, and WhatsApp.